Does a Strong Bicultural Identity Matter for Emotional, Cognitive, and Behavioral Engagement? - Zuzanna M. Preusche; Kerstin Göbel (MDPI AG, 2021)
In the course of their acculturation process, minority students need to negotiate the adaption to the host society's culture and the maintenance of the culture of their country of origin. This identity construction is complex and may encompass contradicting and competing goals. The adjustment to school is seen as a relevant acculturation marker. An increasingly prominent multidimensional construct is students' school engagement because it can provide an insight into the way students feel and interact with the emotional, cognitive, and behavioral domains of school. Successful adjustment to school culture, and acculturation in general, can be closely related to school engagement. There is yet no common knowledge about the role bicultural national and/or ethnic identity plays for the three dimensions of school engagement. The present study focusses on minority students in Germany who report a strong bicultural identity (in comparison with single stronger ethnic or national identities, as well as weaker bicultural identification) to explain students' emotional, cognitive, and behavioral school engagement when controlling for gender, SES, and cultural capital. Data is derived from paper-pencil questionnaires administered in secondary schools in Germany. Regression analyses show that students with a stronger bicultural identity have a significantly higher emotional, cognitive, and behavioral school engagement than their peers with a weaker bicultural identity, when controlling for gender, SES, and cultural capital. The results hint at the relevance of fostering students' ethnic, but also their national, cultural identity to support their school engagement. Implications for teacher education are discussed.